Peran Baznas Kota Kediri Dalam Menunjang Kesejahteraan Masyarakat Miskin - Alif Fatul Choriyah; Sri Abidah Suryaningsih (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This research aims to find out the role of BAZNAS Kediri City in supporting the welfare of the poor. Research methods used by researchers are descriptive qualitative approaches by obtaining data through interviews and then processing and concluding the results of the data The result of this study is that baznas Kediri city plays an optimal role in improving the welfare of poor people by applying sharia Maqashid theory through a superior program, namely the Kediri Cerdas, Kediri Peduli, Kediri Sehat, Kediri Taqwa, and Kediri Makmur programs. With this program, it is able to answer problems for the poor, both in terms of education, health, fulfillment of worship needs, and the fulfillment of basic needs for the fakir every month. So in this case mustahiq can be said to achieve prosperity.